Cabaran membina kemajuan bangsa Melayu dalam matahari memancar tarikh kerajaan Jepun (Challenges to Malay`s progress in matahari memancar tarikh kerajaan Jepun ) - Mohammad Redzuan Othman; Ermy Azziaty Rozali; Roziah Sidek @ Mat Sidek; Ezad Azraai Jamsari (Penerbit UKM, 2011)
Abdullah Abdul Rahman, a religious scholar from Johore, had written about the progress of the Malays in the early 20th century. From 1932 to 1947 he held the post of Head of Johor Religious Department. This article analyzes a work of Abdullah Abdul Rahman, Matahari Memancar Tarikh KerajaanJepun, emphasizing the social aspect, mainly, of the challenges in bringing about progress to the Malays. This study adopts a qualitative approach through document analysis looking at textual materials as the prime sources for this study. This study suggests that Abdullah Abdul Rahman emphasizes the achievements of the Japanese as a committed people in building a nation, whereas the Malays are portrayed as dependent on the colonial master, especially in governance and defence of the state. Apart from that, this study underlines two important characteristics of the Japanese culture then; wisdom and self-confidence. Besides, the significance of this study is substantiated as the positive characteristics of the Japanese could be emulated by the Malays to generate development and progress. In addition, the characteristics have proven to have brought development to the Japanese. The effort to emulate and learn from the achievements and development of the Japanese was when the Malaysian government introduced the Look East Policy in 1982